2016
DOI: 10.21608/bvmj.2016.31298
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriological and molecular studies on toxigenic Staphylococcus aureus in milk and some milk products

Abstract: A total of 200 random samples of milk and milk products represented by kareish cheese, yoghurt and icecream (50 for each) were examined microbiologically for the presence of Staphylococcus aureus, its enterotoxigencity and its antibiotic sensitivity. Staphylococcus aureus was isolated from 8 (16%) milk samples, 15 (30%) kareish cheese, 4 (8%) yoghurt and 11 (22%) ice-cream samples. All S. aureus isolates exhibited clumping factor using kits for reliable latex agglutination test. The susceptibility of the isola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Our finding came in agreement with the previous result [ 36 ] and was higher than the result reported by Abd El-Tawab et al . [ 37 ] where the authors reported sed gene in 36.36% of raw milk samples. In this study, the ELISA test could not identify other classical enterotoxins in subclinical mastitis milk positive for S. aureus and this result agreed with Inganas et al .…”
Section: Discussionmentioning
confidence: 99%
“…Our finding came in agreement with the previous result [ 36 ] and was higher than the result reported by Abd El-Tawab et al . [ 37 ] where the authors reported sed gene in 36.36% of raw milk samples. In this study, the ELISA test could not identify other classical enterotoxins in subclinical mastitis milk positive for S. aureus and this result agreed with Inganas et al .…”
Section: Discussionmentioning
confidence: 99%